An evaluation of the solutions provided by the Rotterdam Rules to identifying the carrier - Renggli, Helen Louise (Shipping Law Unit, 2016)
While the identification of the carrier under a contract for the carriage of goods by sea, whether as unimodal transport or as a leg of a multimodal transport, for the purposes of determining the person liable for the loss or the damage to goods carried, does not generally present a cargo interest with difficulties, there are instances in which it may do so. This minor dissertation evaluates the solutions provided by the Rotterdam Rules to certain 'identity of the carrier problems'.